AIRPORTS AS HETEROTOPIAS: POLITICS AND RESISTANCE UNDER DISCIPLINARY POWER - Uğur Yıldız (İmgelem)
The private/public space dichotomy still holds a significant place in the Western political thought tradition. Hannah Arendt’s idealization of the distinction of the private and public realms in the Ancient Greek polis is no doubt one which essentializes the location with a strict division providing the possibility of the politics and resistance. However, there are certain spaces such as airports moving beyond the classical distinction. Then this paper modifies Arendt’s strict distinction of private/public by focusing on airports as heterotopias. The article admits international airports as heterotopic spaces by following Foucault’s heterotopia and his insight of modern power under the discussion of disciplinary society. This Foucauldian modification of space is presented with the Scene I within the framework of disciplinary power. Even though the Foucauldian insight of power illustrates how it functions by producing and shaping subjects through the assemblage of strategies and techniques, it is limited in terms of the emergence of resistance and politics. By reading the Scene II from Bakhtin’s carnival notion, the article with the argues that there are other spaces beyond private and public spaces in which politics as well as resistance can occur spaces beyond public by benefiting Jacques Rancière’s notion of politics as the disruption of the order.